Architecture Framework for Blockchain Implementation - Lissåker, Felix; Sjöberg, Johan (My University, 2019)
Background: The release of Nakamoto’s whitepaper, describing the inner workings of Bitcoin, triggered a vast interest in blockchain’s core. In resent years, an elevated technological fascination is evident in the large number of new blockchain platforms, tokens and technological solutions aiming to solve the technology’s shortcomings. An enabler of high security, transparency, and auditability, blockchain has been envisioned as the missing piece of the foreseen IoT breakthrough. Industries outside cryptocurrencies are starting to show an elevated interest in the technology. Objective: To facilitate future blockchain implementations, an architecture framework is derived with appropriate viewpoints, models and corresponding guidelines that software architects are recommended to consider. Methods: The framework is empirically constructed following a design science research methodology over three cycles. Challenging scenarios and guidelines are gathered from a workshop with five case company participants, 14 interviews, and a structured literature review including 229 primary studies of which 17 are thoroughly perused. Two industry evaluation sessions with case company representatives assess the framework. An interviewee survey sent out to study participants and a SAPSA conference talk with subsequent feedback from impartial industry representatives further evaluate the work. Results: Beyond well known viewpoints traditionally used in architecture frameworks, five new viewpoints can be derived from the findings. The applicability viewpoint addresses the pronounced difficulty of finding an appropriate use case and using blockchain properly. The ecosystem viewpoint addresses the current scarcity of blockchain expertise and the means by which developers can be supported in their smart contract development. The infrastructure viewpoint highlights how the system’s topology and platform parameters affect its performance, scalability and transaction throughput. The legal viewpoint helps architects taking informed decisions in the light of current legal developments with an accent on network liability and private data management. Lastly, the end user viewpoint attend to the identified prioritization of technological aspects over customer value. Conclusions: The framework need further refinement, e.g. through the addition of extra viewpoints from other frameworks. Nevertheless, the ambition to establish initial implementation practices is satisfied. The viewpoints and their respective guidelines are anticipated to be of industrial value, based on evaluations provided by the case company and other industry representatives.